KONTRIBUSI VOCALOID DALAM PERKEMBANGAN MUSIK DOUJIN DI JEPANG - Paramita Winny (Universitas Pakuan, 2008)
AbstractParamita Winny HapsariThis research uses descriptive method with qualitative approach. This study would like to see the contribution of VOCALOID to the development of doujin music in Japan. Japan with a high level of creativity can make innovations in various things, let alone music. VOCALOID as one of the ways of Japanese innovation in creating a musical masterpiece. VOCALOID is a sound synthesis software that enables users who do not have a vocalist to be able to create the song intact. Doujin works as indie works. Music doujin is a sub category of doujin. VOCALOID-based music is different from doujin music in general. It requires enormous collaboration, which is not centered on a single group in producing the whole work. VOCALOID provides a new color in the development of doujin music in Japan and also stimulates the formation of the next derivative products in Japanese popular culture.Keywords: Music, VOCALOID, Japan